2013
DOI: 10.1063/1.4837617
|View full text |Cite
|
Sign up to set email alerts
|

Influence of explosive density on mechanical properties of high manganese steel explosion hardened

Abstract: The explosion hardening tests of high manganese steel were carried out by using two kinds of explosives of the same composition but different density, respectively. The detonation velocities were tested and the relevant mechanical properties were studied. The results show that the stronger single impulse acting on the specimen, the more hardness of surface increases and the more impact toughness decreases. Compared with the explosive of 1.48 g/cm3 density, the hardness, elongation rate, and impact toughness of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…It leads to greater ductility of sample than in case of heat treatment. Explosive hardening method has also been reported by Hu et al [15,16].…”
Section: Civil Applicationsmentioning
confidence: 84%
“…It leads to greater ductility of sample than in case of heat treatment. Explosive hardening method has also been reported by Hu et al [15,16].…”
Section: Civil Applicationsmentioning
confidence: 84%
“…Pre-hardening treatment can mainly be applied by shot peening [15,16], laser shock peening [17], explosion hardening [18,19], and mechanical impact [20] to modify the microstructure and improve the hardness of the top surface and subsurface, resulting in enhanced initial wear and deformation resistance for extended service life. Beheshti et al [15] investigated the influence of austenitizing temperature, time, and shot peening on grain size and microstructure of Hadfield steel.…”
Section: Introductionmentioning
confidence: 99%
“…But laser shock peening technology has not widely been used because of high-cost equipment. Hu et al [18] studied the effect of two kinds of explosives with the same composition and different densities on the mechanical properties of high manganese steel. They found that stronger single impulse acting on the sample resulted in increased surface hardness and decreased impact toughness.…”
Section: Introductionmentioning
confidence: 99%